2012
DOI: 10.3928/01477447-20121120-33
|View full text |Cite
|
Sign up to set email alerts
|

Fusion After Interspinous Device Placement

Abstract: Lumbar interspinous devices are intended to unload the facet joints, restore foraminal height, lower intradisk pressure, and provide motion-preserving stabilization. They are an alternative treatment for patients with spinal degeneration and have increased in popularity in recent years. To the authors' knowledge, heterotopic ossification has not been previously reported around an interspinous device, and this is the first reported case of interspinous fusion after interspinous device placement.A 66-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…While the traditional approach is still followed by most surgeons, there is growing evidence of the greater safety of these innovative procedures in properly selected patients. 13 The traditional posterior midline approach has been associated with significant complications, such as muscle necrosis, muscular denervation, reduced muscular pressure, ischemia, damage to revascularization, and ligament damage. 14,15 In an effort to minimize the kinds of complications associated with the open technique, minimally invasive procedures assisted by technology have begun to be used for all regions of the spine and for procedures of decompression, arthrodesis, instrumentation, and the placement of interspinous spacers.…”
Section: Discussionmentioning
confidence: 99%
“…While the traditional approach is still followed by most surgeons, there is growing evidence of the greater safety of these innovative procedures in properly selected patients. 13 The traditional posterior midline approach has been associated with significant complications, such as muscle necrosis, muscular denervation, reduced muscular pressure, ischemia, damage to revascularization, and ligament damage. 14,15 In an effort to minimize the kinds of complications associated with the open technique, minimally invasive procedures assisted by technology have begun to be used for all regions of the spine and for procedures of decompression, arthrodesis, instrumentation, and the placement of interspinous spacers.…”
Section: Discussionmentioning
confidence: 99%
“…In some literature reports [28], heterotopic bone formation around a dynamic interspinous device is a potential mid-and long-term complication, which may hamper motion preservation. However, in our opinion, heterotopic ossification around the Coflex device is not necessarily a bad thing.…”
Section: Coflex Device-related Complicationsmentioning
confidence: 99%
“…1,2 Many studies have shown that disk degeneration develops as a result of the excessive movement and overload in the proximal and distal adjacent levels during fusion operations and that instability, disk height loss, foraminal and central stenosis, or facet joint arthrosis develop as a consequence of the degeneration; this new condition is referred to as an "adjacent segment problem." [3][4][5] In this study, between January 1994 and July 2005, we evaluated 23 patients who had undergone fusion surgery, seeking radiologic evidence of L5-S1 disk degeneration under the fusion region over a 10-year follow-up period. In patients who did have degeneration, we assessed whether it was compatible with their clinical signs.…”
mentioning
confidence: 99%